Women’s perceptions of the helpfulness of strategies for coping with intimate partner violence - Renner, Lynette M. (Journal of family violence, 2022)
Using the Intimate Partner Violence Strategies Index (IPVSI), we assessed women’s strategy use and the helpfulness of these strategies in preventing, stopping, or coping with intimate partner violence (IPV). We further examined which strategies women found most and least helpful and why, associations between strategy use and types of IPV experienced, and differences in strategy use and helpfulness by select demographic variables. We used data from Wave 1 of a two-year panel study of women who experienced IPV victimization and received civil legal services. The IPVSI includes 39 strategies across six categories: formal network, legal, safety planning, informal network, resistance, and placating. We collected data on women’s perceptions of the most and least helpful strategies and why, and whether they used other strategies not listed on the IPVSI. We used descriptive, bivariate, and content analyses to answer the research questions. Women used an average of 21 strategies. Placating, resistance, informal network, and legal strategies were the most frequently used; however, women rated resistance and placating strategies as least helpful and informal network strategies as most helpful. IPV types (physical, nonphysical) were differentially associated with the number and types of strategies used. Women expressed why strategies were helpful or unhelpful, along with what other strategies they used. Models of IPV help-seeking have evolved from viewing women as passive to seeing them as actively engaging in many private and public strategies to manage, prevent, and escape violence. Our findings highlight some discrepancies between what is used and what works.